A generalized purification step for viral particles using mannitol flocculation. (5th July 2018) - Heldt, Caryn L.; Saksule, Ashish; Joshi, Pratik U.; Ghafarian, Majid
Abstract : Vaccine manufacturing has conventionally been performed by the developed world using traditional unit operations like filtration and chromatography. There is currently a shift in the manufacturing of vaccines to the less developed world, requiring unit operations that reduce costs, increase recovery, and are amenable to continuous manufacturing. This work demonstrates that mannitol can be used as a flocculant for an enveloped and nonenveloped virus and can purify the virus from protein contaminants after microfiltration. The recovery of the virus ranges from 58 to 96% depending on virus, the filter pore size, and the starting concentration of the virus. Protein removal of 80% was achieved for the small nonenveloped virus using a 0.1 µm filter because proteins were not flocculated with the virus and flowed through the filter. It is hypothesized that mannitol dehydrates the viral surface by controlling the water structure surrounding the virus. Without the ability to become compact, as occurs with proteins, the virus aggregates in the presence of osmolytes and proteins do not. Osmolyte flocculation is a scalable process using high flux microfilters. It has been applied to both an enveloped and nonenveloped virus, making this process friendly to a variety of vaccine and gene therapy products. © 2018 American Institute of Chemical Engineers Biotechnol. Prog., 34:1027–1035, 2018